Analisis Semikuantitatif Parasetamol Dalam Jamu Pegal Linu Menggunakan Pemrosesan Gambar Digital dari Hasil Kromatografi Lapis Tipis - Fernanda, M.A. Hanny Ferry; Wardani, Ratih Kusuma (Brawijaya University, 2022)
Jamu is a pharmaceutical preparation derived from plant simplicia and must meet quality requirements, one of which is that it must not contain medicinal chemicals (BKO). One of the herbs widely circulated and can be obtained freely in the community is herbal medicine for aches and pains. In herbal aches and pains, paracetamol is the BKO suspected to be used in this preparation. This study aimed to develop an analytical method to determine the content of paracetamol BKO in herbal pain relief semi-quantitatively using digital images obtained from Thin Layer Chromatography. The semi-quantitative analysis method is carried out by processing digital images using the qTLC application. The results of this study proved the presence of paracetamol BKO in herbal aches and pains qualitatively using the TLC method. Of the five samples analyzed, only one contained paracetamol BKO with an Rf value of 0.15, while the standard Rf was 0.14. The analysis was then continued with the determination of paracetamol levels semi-quantitatively using digital image processing from the Thin Layer Chromatography results. Based on the results of semi-quantitative analysis, it can be seen that the sample suspected to contain paracetamol contains paracetamol with a concentration of 1,491.31 ppm. The results of this study can provide accurate detection of paracetamol BKO compound determination and semi-quantification limits and have the potential for more quantitative analysis in herbal medicine.